Esensial Imparsialitas dalam Penyelesaian Sengketa Hubungan Industrial - Enge Christina; Wiraatmaja Lookman (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
In the modern industrialization era, industrial relations disputes are increasing in both quantity and complexity. This condition demands a fast, precise, fair, and efficient dispute resolution mechanism. In accordance with the provisions of laws and regulations, mandatory settlement efforts must first be pursued through bipartite or tripartite negotiations through deliberation to reach a consensus, known as Alternative Dispute Resolution (ADR). ADR is a dispute resolution mechanism outside the court that is oriented towards a win-win solution, namely an agreement that accommodates the interests of all parties. However, in practice, the implementation of mediation in Industrial Relations Disputes (PHI) still faces various obstacles, particularly related to the lack of the principle of impartiality of the mediator. This study uses a normative juridical method with a statutory approach and a conceptual approach. The results of the study indicate that the PHI Mediator is an administrative position attached to the state civil apparatus, not an independent profession. The absence of strict sanctions for violations of the code of ethics, limited mediation time, and the absence of conflict of interest regulations in the Minister of Manpower Regulation No. Law No. 17 of 2014 makes the mediator vulnerable to intervention by certain parties. This situation has implications for the emergence of recommendations that are potentially non-objective and detrimental to one of the parties. Therefore, the principle of impartiality is a fundamental element in Industrial Relations (PHI) mediation to ensure a fair, balanced, and substantively just dispute resolution.